Inventarisasi Jenis Ikan Hias Yang Tertangkap Di Perairan Pulau Serangan - I Putu Agung Baira Dhanandjaya; Ima Yudha Perwira; Suprabadevi Ayumayasari Saraswati; Gde Raka Angga Kartika (Samakia : Jurnal Ilmu Perikanan, 2025)
This study investigated the relationship between habitat substrate, water quality parameters and ornamental fish distribution in the waters of Serangan Island, Bali. Using a community ecology approach, this study found that coral substrate supported higher diversity and abundance of ornamental fish species than sand and coral-sand substrate. Water quality parameters such as dissolved oxygen, salinity, water brightness and pH showed significant influence on species distribution. Species identification provided detailed data on morphology, meristics and conservation status based on the IUCN Red List. These results confirm the importance of coral habitat conservation and water quality management to support the sustainability of ornamental fish populations in the region